REDESAIN ASRAMA HAJI ACEH, TEMA: GREEN ARCHITECTURE - Ahmadi, Ahmadi; Aidina, Faiza (Rumoh Journal of Architecture, 2021)
The redesign of the Aceh Hajj Dormitory was motivated by the condition of the building which was felt to be inadequate to facilitate the activities that would be accommodated during the operational service of the Hajj season. Some of the problems related to the Hajj dormitory building are the condition of the building that is old and damp, the room capacity is not sufficient due to the number of Hajj groups that increase every year, and some infrastructure facilities that do not exist in the building and must be met regarding service operational requirements. The design of the outer space of the building also requires special attention, such as adjusting the distance between buildings to match the zoning hierarchy and more regular parking arrangements and manage entry-exit circulationin order not to make any congestion during the hajj season. The redesign project is located on Jalan T. Nyak Arif, Lingke, Kuta Alam District, Banda Aceh. The redesign intention is to provide comfort and adequate facilities for pilgrims according to their needs and functions. The Classification of the Redesign of the Aceh Hajj Dormitory is a Type of Embarkation Hajj Dormitory, the Technical Implementation Unit of the Directorate General of Hajj and Umrah. This plan applies the theme of Green Architecture by utilizing conditions and natural energy sources, responding to the site conditions of the building and paying attention to building users. The analysis used in this building is functional analysis, site analysis and building analysis. The redesign of the Aceh Hajj Dormitory applies the use of rainwater and the application of a vertical garden. Land area 25,300 m2. High-mass and low-rise buildings, the Building Base Coefficient (KDB) is 151,800 m2 and the total building area is 50,600 m2. The redesign of the Aceh Hajj Dormitory has 84 rooms with a capacity of one room for 4 people. Supporting facilities include canteens, mosques and security posts.